Уточнена термомеханічна модель вимушених гармонічних коливань фізично нелінійної оболонки з розподіленими трансверсально-ізотропними сенсорами - Карнаухов, В.Г.; Жук, Я.О.; Карнаухова, Т.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Using the refined Timoshenko's hypotheses and similar hypotheses for electric field quantities, a thermomechanical model of thin-walled shells with distributed transversely isotropic sensors with regard for dissipative heating and physical nonlinearities is presented. Several types of electric boundary conditions are considered, when electrodes on a sensor are short-circuited or open. The formulas for sensor's indices are obtained for different boundary conditions.